Militarization of police: a comparison of police paramilitary units in Canadian and the United States - Cyr, K. (International journal of police science & management, 2020)
In comparison with Canada, the more pronounced ability to acquire special weapons and tactics (SWAT) equipment in the United States suggests the resulting proliferation of SWAT teams with adequate material resources is likely to continue. This proliferation has stimulated media and public discourses against the “militarization” of police. In Canada, however, the amalgamation of SWAT teams has led to increased standardization in SWAT training, member specialization and protocols of applied practice. We argue that, in comparison with the United States, the proliferation of paramilitary activity is limited in the Canadian policing landscape by public safety governance structures, acquisition processes, and judicial scrutiny. In consequence, Canadian police services are better positioned than their counterparts in the United States to withstand the public scrutiny tied to police tactical responses.